1999
DOI: 10.1088/0029-5515/39/5/101
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on neoclassical tearing mode stabilization by ECCD in ASDEX Upgrade

Abstract: The reduction of neoclassical tearing modes by ECCD is demonstrated experimentally. It is shown that with an averaged ECCD power of only 4-8% of the total heating power injected into the discharge, the island width can be reduced by 40%, provided that the centre of deposition is very close to the resonant surface. The reduction in mode amplitude results in a partial recovery of the loss of stored energy induced by the mode. This experimental result is well reproduced by modelling calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
149
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(156 citation statements)
references
References 8 publications
7
149
0
Order By: Relevance
“…3 NTM suppression experiments have been performed successfully using both ECRH and ECCD. [4][5][6][7][8][9][10][11][12][13][14] The generalized Rutherford equation (GRE) 15,16 provides a theoretical model for the growth and stabilization of tearing modes. It describes the nonlinear temporal evolution of the full width w of the associated magnetic island as a function of different stabilizing and destabilizing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…3 NTM suppression experiments have been performed successfully using both ECRH and ECCD. [4][5][6][7][8][9][10][11][12][13][14] The generalized Rutherford equation (GRE) 15,16 provides a theoretical model for the growth and stabilization of tearing modes. It describes the nonlinear temporal evolution of the full width w of the associated magnetic island as a function of different stabilizing and destabilizing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…By the time of the previous review [5], the suppression of (m=3,n=2) NTMs had been demonstrated in several tokamaks [24], [25], [26] and [27] and first experiments on partial (2,1) suppression had been carried out. Also, first attempts at feedback control of the deposition had been made.…”
Section: Application Of Ecrh and Eccd For Optimization Of Plasma Stabmentioning
confidence: 99%
“…In that respect, steady progress has been made at DIII-D, ASDEX-U, and JT60-U with regard to controlling NTMs using Electron Cyclotron Current Drive ͑ECCD͒. [37][38][39] For instance, the full suppression of magnetic islands has been achieved in some cases, with the added benefit that the plasma ␤ can be increased above the limiting instability threshold. Recent computational studies 8 have shown that a combined power of 25 MW might be required to control the 3 / 2 and 2 / 1 modes in ITER.…”
Section: -12mentioning
confidence: 99%